The Geography Teacher Practices in Implementation of Formative Assessment: A Case Study - Mutalib, Suzana Abd; Ahmad, Jamil (EDUCARE, 2014)
ABSTRACT: Teachers need the necessary skills and further awareness and understanding in order to implement formative assessment activities effectively in their T&L (Teaching & Learning) process. Formative assessment is an ongoing process during the process of teaching and learning. Â A proper implementation of the true concept of formative assessment will have positive impacts on studentsâ learning and motivation. This paper reports the findings of a qualitative study undertaken to determine whether formative assessment is accurately implemented as per recommendation of experts in the teaching and learning process of the subject of geography. Data was obtained through classroom observations and interviews with two Geography teachers. Fieldwork was done at a secondary school in the state of Perak, Malaysia. Overall, the findings of the study show both teachers practises formative assessment as recommended by experts. Both teachers also displayed outstanding performance in their application of some of the concept of formative assessment. However, there are also rooms for improvements especially in the area of implementation of formative assessment activities. Therefore, all concerned parties must sit together to discuss necessary steps that must be taken to ensure the implementation of high quality formative assessment. Efforts must be undertaken to ensure that teachers are properly educated of the proper concept of formative assessment and its implementation in the classroom.KEY WORDS: Formative assessment, the implementation of formative assessment in teaching and learning process, formative assessment in geography.About the Authors: Suzana Abd Mutalib is a Student at the Faculty of Education UKM (National University of Malaysia); and Dr. Jamil Ahmad is a Lecturer at the Faculty of Education UKM, Bangi, Selangor Darul Ehsan, Malaysia. For academic purposes, the authors can be contacted via e-mails at: suzanaalea@yahoo.com.my and jamil3191@yahoo.co.ukHow to cite this article? Mutalib, Suzana Abd & Jamil Ahmad. (2014). âThe Geography Teacher Practices in Implementation of Formative Assessment: A Case Studyâ in EDUCARE: International Journal for Educational Studies, Vol.7(1) August, pp.75-84. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877.Chronicle of the article: Accepted (November 23, 2013); Revised (April 1, 2014); and Published (August 17, 2014).